The Humboldtian tradition : origins and legacies - Josephson, Peter; Karlsohn, Thomas, 1967-; Östling, Johan, 1978- (History of science and medicine library. Scientific and learned cultures and their institutions ;, 2014)
In The Humboldtian Tradition, eleven scholars analyse Wilhelm von Humboldt as a historical phenomenon and a contemporary symbol. They put Humboldt's basic academic principles into context and discuss their significance for the current debate about the university.